Un pliego de romances perdido. - MARTOS, JOSEP LLUÍS (Scripta, 2023)
The Antwerp printer Martín Nucio used a poetic printed sheet in two editions of 1546. This edition is lost, but there is a trace of it in three later poetics sheets. In this paper, the relationship of these late prints with the lost sheet is delimited and their editorial data is reconstructed. For this, the textual and iconographic affiliation of the poems and the preserved prints are studied, as well as the editorial uses of the printing press that printed the lost sheet. Likewise, the sources of this poetic genre in the editions of Martín Nucio are studied and attention is paid to his training stay in Spain.